A herbal preparation from Azadirachta indica as an alternative to conventional control against coccidia in village chickens - Yaacob, Mohd Fawwaz (2017)
A study was conducted to evaluate the number of oocytes in village chicken and body weight of the village chicken.In general, the experiment was carried out to determine the effectiveness of dietary inclusion of Neem leaves in prevention of coccidiosis. The specific objectives were to determine the effectiveness of dietary inclusion of Neem leaves in prevention of coccidiosis in village chicken, and to study the effect of dietary Neem leaves on the growth performance of village chicken. The total number of the chicken were used to calculate the number of oocytes and body weight of the chicken were 27 chickens. This experiment was conducted at Unit Poltri, Ladang 2, Universiti Putra Malaysia, parasitology laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia and Nutritional Laboratory, Department of Animal Science, Faculty of Agriculture, Universiti Putra Malaysia. The experimental unit were Azadirachta indica (Neem leaves), Gallus gallus domesticus (UPM village chicken) and coccidiostat (AM-COCC, Vetpharm Lab(S) Pte Ltd). There were three treatment in this study. The first treatment was the village chicken grower diet (control diet). Second treatment is the control diet with Neem leaves at 10% level and the last treatment was control diet with 1% of coccidiostat. The design of this experiment was Complete Randomized Design. There were three treatments as mentioned above. The UPM village chicken were selected from a flock aged 8 weeks that have been raised under free range system for about 4 weeks before commencement of the experiment. The chicken then were placed randomly into the broiler cages. The Neem leaves was collected, dried in the oven for 48 hours at 60°C and then ground and mixed with the grower feed. The chicken were fed according to the treatment. The faecal samples (oocyte counts) and bodyweight were take on weekly basis. From the experiment, it was found that treatment 1 had significantly higher oocyte counts than treatment 2 and treatment 3. However, between treatment 2 and 3 were not significant. The number of oocytes in treatment 2 and 3 rapidly decrease until below the critical level of 300 OPG that can result in coccidial infection. Treatment 1 shows decrease in the number of oocytes but still remain at infective level. For the body weight of the village chicken, it was found that there were no significant differences in bodyweight between treatment 1, treatment 2 and treatment 3. Despite the very high oocytes count in Treatment 1, the UPM village chicken showed positive growth without exhibiting clinical signs such as blood tinged feaces. Throughout this study, it shown that Neem leaves has anticoccidial effect. It also can be used to replace coccidiostat.